EIF Venture Capital Survey 2021: Market sentiment - Antonia Botsari; Kilian Kiefer; Frank Lang; Davide Legnani (European Investment Fund (EIF), 2021)
The EIF VC Survey, the EIF Private Equity Mid-Market Survey, and the EIF Business Angels Survey (the largest combined regular survey exercises among GPs and Business Angels on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2021 EIF VC Survey. The paper focuses on the market sentiment and the impact of COVID-19. The study looks at the current situation, developments in the recent past and expectations for the future. The main results are summarised and compared over time. The publication provides a valuable picture of the developments and the market situation in 2021 as well as an outlook for the near future.
Keywords: 330